MANAJEMEN KEPEMIMPINAN KEPALA SEKOLAH TERHADAP KINERJA GURU SMP TARUNA JAYA - Yanto, Deri (UNISAN JURNAL, 2024)
The purpose of this study was to find out the principal’s leadership management on teacher performance at SMP Taruna Jaya. This study used a qualitative approach. While the method used in this research is descriptive research method. The data collection technique used is observation, interview and documentation techniques. This participatory observation technique was carried out to observe the geographical location in the form of a location plan and environmental conditions, vision, mission, strategy and motto of the school as well as the state of the Principal’s Leadership Management on Teacher Performance at SMP Taruna Jaya. Interviews were conducted to determine the stages of curriculum development. Based on the results of the description that has been described, the curriculum development management process cannot be separated from Team Work (cooperation) with the help of supporting resources. Implementation with a certain strategy that is effective and efficient, and refers to the vision, mission and goals that have been determined previously. that the Principal’s Leadership Management on teacher performance at SMP Taruna Jaya, is very important, the role of a leader, namely the principal as a Manager in improving teacher performance. .The leadership of the principal’s management includes the implementation of planning (Planning), the principal has carried out the school’s vision and mission, and has prepared long-term plans and short-term plans for the school.